Shopping centres beyond purchasing of luxury goods: A tourism perspective - Brochado, A.; Oliveira, C.; Rita, P.; Oliveira, F. (Annals of Leisure Research, 2019)
This study sought to identify the main dimensions of shopping experiences shared online by tourists after visiting luxury shopping centres and to ascertain the main narratives linked with any dissatisfaction these tourists express. A mixed content analysis was conducted on 1050 reviews describing shopping experiences in seven luxury shopping centres. The results reveal the existence of eight dominant themes: shopping, luxury, day, place, food, walk, expensive (goods) and people. The main theme linked with dissatisfaction is that of expensive. The concept map of these themes confirms that experiences in luxury shopping centres diverge from those in general goods shopping centres.